2021
DOI: 10.1371/journal.ppat.1009421
|View full text |Cite
|
Sign up to set email alerts
|

N6-methyladenosine modification of HIV-1 RNA suppresses type-I interferon induction in differentiated monocytic cells and primary macrophages

Abstract: N6-methyladenosine (m6A) is a prevalent RNA modification that plays a key role in regulating eukaryotic cellular mRNA functions. RNA m6A modification is regulated by two groups of cellular proteins, writers and erasers that add or remove m6A, respectively. HIV-1 RNA contains m6A modifications that modulate viral infection and gene expression in CD4+ T cells. However, it remains unclear whether m6A modifications of HIV-1 RNA modulate innate immune responses in myeloid cells that are important for antiviral immu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 65 publications
1
47
0
Order By: Relevance
“…Through preventing the addition of 2′-O-methyl marks to HIV-1 gRNA by siRNA mediated FTSJ3 knockdown, the authors show that incoming gRNA induces IFN-α and IFN-β expression. Since this work was published four further studies exploring innate immune sensing of viral RNA were published by Lu et al [ 37 ], Chen et al [ 35 ], Kim et al [ 34 ] and Lu et al [ 42 ] demonstrating, in a similar manner to Ringeard et al, that HMPV, HIV-1, HBV/HCV, VSV, MeV and SeV RNAs are also modified to avoid detection by the host cell. In each of these cases, the viral RNA of each virus is m 6 A modified and this is found to prevent recognition by RIG-I, in validation of the phenomenon described previously by Durbin et al These studies perform experiments to reduce the modification of virally encoded adenosines using methods such as mutation of the viral genome or treatment with 3-deazaadenosine (DAA), an inhibitor of S-Adenosylhomocysteine (SAH) hydrolase and find that this in turn increases the cellular type 1 interferon response to infection.…”
Section: Immune Evasion By Viral Rnamentioning
confidence: 99%
“…Through preventing the addition of 2′-O-methyl marks to HIV-1 gRNA by siRNA mediated FTSJ3 knockdown, the authors show that incoming gRNA induces IFN-α and IFN-β expression. Since this work was published four further studies exploring innate immune sensing of viral RNA were published by Lu et al [ 37 ], Chen et al [ 35 ], Kim et al [ 34 ] and Lu et al [ 42 ] demonstrating, in a similar manner to Ringeard et al, that HMPV, HIV-1, HBV/HCV, VSV, MeV and SeV RNAs are also modified to avoid detection by the host cell. In each of these cases, the viral RNA of each virus is m 6 A modified and this is found to prevent recognition by RIG-I, in validation of the phenomenon described previously by Durbin et al These studies perform experiments to reduce the modification of virally encoded adenosines using methods such as mutation of the viral genome or treatment with 3-deazaadenosine (DAA), an inhibitor of S-Adenosylhomocysteine (SAH) hydrolase and find that this in turn increases the cellular type 1 interferon response to infection.…”
Section: Immune Evasion By Viral Rnamentioning
confidence: 99%
“…2-O methylated HIV-1 RNA is not sensed effectively by the cytosolic RNA sensors Melanoma-Differentiation-Associated Gene 5 (MDA5) and RIG-I. In HIV-1-infected dendritic cells and macrophages, the adenosine methylation (N6-methyladenosine) of HIV-1 genomic RNA correlated with resistance against IFN-mediated immune responses ( 39 ). The cellular writers, such as methyltransferase-like METTL3 and METTL14, add a methyl group to adenosine and erasers, such as fat mass and obesity-associated protein (FTO) and α-ketoglutarate dependent dioxygenase AlkB homolog-5 (ALKBH5), remove the methyl groups from mRNA.…”
Section: Counter Mechanisms By Hiv-1 To Evade Intracellular Intrinsic Immunitymentioning
confidence: 99%
“…The cellular writers, such as methyltransferase-like METTL3 and METTL14, add a methyl group to adenosine and erasers, such as fat mass and obesity-associated protein (FTO) and α-ketoglutarate dependent dioxygenase AlkB homolog-5 (ALKBH5), remove the methyl groups from mRNA. The HIV-1 produced by HEK293T cells overexpressing FTO or ALKBH5 enhanced induction of IFNs in the target cells by decreasing adenosine methylation in its genome and thus preventing the activation of IRF3 and IRF7, suggesting the importance of host-directed HIV-1 RNA modification in the immune evasion strategy ( 39 ).…”
Section: Counter Mechanisms By Hiv-1 To Evade Intracellular Intrinsic Immunitymentioning
confidence: 99%
“…Additionally, m6A reader proteins (YTHDF1-3) can both positively and negatively affect different steps in the life cycle of the virus [ 5 , 164 , 165 , 166 ]. A recent study demonstrated that in myeloid cells (monocytes and macrophages) the m6A modification in HIV-1 RNA can suppress Type I IFN expression, and when the m6A modification is altered/defective, the affected RNA is sensed by RIG-1 [ 128 ]. However, to date, no studies have directly linked the IFN/ISG response and the m6A modification in macrophages that serve as replication-competent latent HIV-1 reservoirs.…”
Section: The Regulation Of the Ifn/isg Signaling Network In Hiv-1-infected Cellsmentioning
confidence: 99%